Early malfunction of a biliary self-expandable metal stent with an antireflux valve: A case report. Issue 16 (April 2020) - Kim, Sang Hoon; Oh, Chi Hyuk; Jae, Min Lee; Choi, Seong Ji; Choi, Hyuk Soon; Kim, Eun Sun; Keum, Bora; Jeen, Yoon Tae; Chun, Hoon Jai; Lee, Hong Sik; Kim, Chang Duck
Abstract: Rationale: Biliary drainage is essential to resolve jaundice in patients with malignant biliary obstruction. Recently, a biliary self-expandable metal stent (SEMS) with an antireflux valve was developed to prevent enteric-biliary reflux. Its antireflux valve was made of expanded polytetrafluoroethylene (ePTFE), a biostable and biocompatible material. Changes of the ePTFE membrane of medical devices are rarely reported in clinical practice. Patient concerns: A 59-year-old woman was admitted with a complaint of jaundice. Around 1 month before, she underwent endoscopic biliary stenting using a SEMS with an antireflux valve. Diagnosis: Acute cholangitis due to stent clogging was detected on abdominal computed tomography. Interventions: Endoscopic retrograde cholangiopancreatography and removal of the SEMS with deformity were performed. Outcomes: The obstructive jaundice was rapidly resolved after the removal of the clogged stent. Lessons: Although the ePTFE membrane is widely used to make medical devices, unexpected changes could occur after the membrane is exposed to bile juice in the duodenum. When performing biliary stenting using a SEMS with an antireflux valve, both the risk of early malfunction and the benefit of the antireflux effect should be considered. Abstract : Supplemental Digital Content is available in the text